A Panel of Serum MiRNA Biomarkers for the Diagnosis of Severe to Mild Traumatic Brain Injury in Humans - Bhomia, Manish (Sci Rep, 2016)
MicroRNAs (MiRNAs) are small endogenous RNA molecules and have emerged as novel serum diagnostic biomarkers for several diseases due to their stability and detection at minute quantities. In this study, we have identified a serum miRNA signature in human serum samples of mild to severe TBI, which can be used for diagnosis of mild and moderate TBI (MMTBI). Human serum samples of MMTBI, severe TBI (STBI), orthopedic injury and healthy controls were used and miRNA profiling was done using taqman real time PCR. The real time PCR data for the MMTBI, STBI and orthopedic injury was normalized to the control samples which showed upregulation of 39, 37 and 33 miRNAs in MMTBI, STBI and orthopedic injury groups respectively. TBI groups were compared to orthopedic injury group and an up-regulation of 18 and 20 miRNAs in MMTBI and STBI groups was observed. Among these, a signature of 10 miRNAs was found to be present in both MMTBI and STBI groups. These 10 miRNAs were validated in cerebrospinal fluid (CSF) from STBI and four miRNAs were found to be upregulated in CSF. In conclusion, we identified a subset of 10 unique miRNAs which can be used for diagnosis of MMTBI and STBI.